2014
DOI: 10.1016/j.cplett.2014.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope-phase dependence of asymmetric C D bond breaking in C2D2 in an intense few-cycle laser field

Abstract: The carrier envelope phase (CEP) dependence in the CAD bond breaking of C2D2 induced by an intense few-cycle laser pulse is investigated. The ejection direction of D+ ions generated from the Coulomb explosion, C2D2þ 2 ! C2Dþ and D+, exhibits the CEP dependent asymmetry, while its CEP dependence is out of phase by p with respect to the CEP dependence of the recoil momentum of C2Dþ2 . From a recollisional double ionization model, the asymmetry in the ejection direction of D+ was ascribed to the laser-assisted CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
(27 reference statements)
0
33
0
Order By: Relevance
“…In particular, a strong CEP dependence in the total fragmentation yield has been reported [30]. Moreover, it has been demonstrated that controlling the CEP permits selective breaking of either C-H bond, leading to directional proton emission [32,33]. Very recently, we have reported on the control of the preferential direction of hydrogen migration in acetylene and allene [34], and toluene [35] using the CEP of a few-cycle laser pulse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a strong CEP dependence in the total fragmentation yield has been reported [30]. Moreover, it has been demonstrated that controlling the CEP permits selective breaking of either C-H bond, leading to directional proton emission [32,33]. Very recently, we have reported on the control of the preferential direction of hydrogen migration in acetylene and allene [34], and toluene [35] using the CEP of a few-cycle laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35]). CEP effects in the deprotonation of acetylene, induced by few-cycle laser pulses, have attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…A recent experiment showed the evidence of O 2 formation from CO 2 molecules after UV excitation through the detection of C + [5]. So far, O 2 formation from CO 2 has not been directly observed.In the past decade, intense ultrashort laser pulses have been successfully applied to trigger and control molecular reactions such as dissociation and isomerization [6][7][8][9][10][11][12][13][14][15]. When a molecule interacts with a strong laser field, electrons from outer molecular orbitals can be excited or removed through tunneling or over-the-barrier ionization which may prepare the molecule in an excited state or a state with a certain charge.…”
mentioning
confidence: 99%
“…The experimental setup for the generation of linearly polarized few-cycle laser pulses and the detection of fragment ions have been described previously [6]. The experimental setup consists of (i) a chirped-pulse-amplification femtosecond Ti:sapphire laser system, (ii) a pulse compression system to generate few-cycle laser pulses [7] and (iii) an ultrahigh vacuum chamber for CMI measurements [8].…”
Section: Methodsmentioning
confidence: 99%